Design optimization of an oscillating water column wave energy converter: analytical and numerical modeling - Mendonça, A. C. (2017)
An analytical model is applied to a schematic case of an oscillating water column (OWC), without head loss, to obtain a first estimation of the chamber hydraulic efficiency. The IH2VOF numerical model of wave-structure interations is applied to perform an investigation, useful to complement and verify the analytical approach and analyses the flow characteristics on the OWC, including nonlinear effects. The numerical model was validated against physical model tests on a schematic OWC stucture at the National Laboratory of Civil Engineering, presenting god agreement. A significant difference of amplification factor parameter was observed between lhe analytical results and numerical results and experimental data, which may be attributed to the absence of head loss in the analytical model.